2016
DOI: 10.1002/oa.2483
|View full text |Cite
|
Sign up to set email alerts
|

An Osteobiography of a 19th‐Century Dog from Toronto, Canada

Abstract: A 19 th -century dog burial uncovered from a historical homelot in Toronto, Canada, provided a unique opportunity to reconstruct the individual's osteobiography. Of particular interest are the dog's very large size and a suite of skeletal pathologies. Recovery of a nearly complete skeleton combined with the use of x-rays and micro-computed tomography (micro-CT) allowed for a discriminating differential diagnoses. Stable isotope analyses were applied to investigate questions of diet. Results reveal an individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Reduced variability in shoulder height seen in Native American dogs from eastern North America does not preclude selection for specific purposes (e.g., consumption, hunting, fibre, or traction) but suggests that those roles did not require the extreme differences in body size and shape found in European dogs (Figures and ). Future investigations integrating aDNA (Leathlobhair et al, ), the congenital absence of permanent P 1 and M 3 observed in many North American dogs (Crockford, ; Warren, ), and multivariate morphometric analyses of cranial shape (Phillips, Baxter, & Nussbaumer, ; Tourigny et al, ) may further illuminate these questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced variability in shoulder height seen in Native American dogs from eastern North America does not preclude selection for specific purposes (e.g., consumption, hunting, fibre, or traction) but suggests that those roles did not require the extreme differences in body size and shape found in European dogs (Figures and ). Future investigations integrating aDNA (Leathlobhair et al, ), the congenital absence of permanent P 1 and M 3 observed in many North American dogs (Crockford, ; Warren, ), and multivariate morphometric analyses of cranial shape (Phillips, Baxter, & Nussbaumer, ; Tourigny et al, ) may further illuminate these questions.…”
Section: Discussionmentioning
confidence: 99%
“…Biomorphometrics has the potential to further our understanding of selective pressure, breed differences, and breed improvement (Albarella, 1997(Albarella, , 1999(Albarella, , 2002Phillips et al, 2009;Tourigny et al, 2015) and has provided the foundation for many of these analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This commentary is a call for greater attention to the naturally occurring phenomenon of FA and for a more intense collaboration among archaeologists and veterinarians with relevant morphological and pathological experience. Such cooperation is not new in the human (Mays, ) and animal research (Janssens, Street, et al, ; Janssens, Giemsch, Schmitz, Street, & Van Dongen, ; Lawler, Reetz, Sackman, Evans, & Widga, ; Tourigny et al, ), but it does remain uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact origins of this relationship remain somewhat obscure (Miklosi, 2007;Larson et al, 2012), the close association of dogs and humans in cultural contexts lend special significance to dog evolution and behavior (Morey, 2006(Morey, , 2010. Paleopathological studies can contribute new understandings of the nature of human-dog relationships through analyses of behaviorallyinfluenced damage to bones and joints, or diseases and injuries sustained through life activities (Snyder, 1995;Tourigny et al, 2015). Dog paleopathology specifically has the potential to inform about subsistence or mobility strategies among human groups (Warren, 2004;.…”
Section: Introductionmentioning
confidence: 99%
“…Previous paleopathological studies of domestic dogs have focused on opportunistic observations of gross pathologies (Warren, 2004;Walker et al, 2005;Ware, 2006). Only rarely (Tourigny et al, 2015) have such studies incorporated medical imaging (radiology and tomography) or rigorous differential diagnosis, despite example work in human paleopathology (Miller et al, 1996;Ortner, 2003;Lynnerup, 2010) and forensics (Jalalzadeh, H. et al, 2015).…”
Section: Introductionmentioning
confidence: 99%